Multidrug resistance markers in acute myeloid leukemias - O. D. Zakharov; Ye. Yu. Rybalkina; M. A. Volkova; A. A. Stavrovskaya (Онкогематология)
Multidrug resistance (MDR) is the cell resistance to a number of drugs. Proteins from the ABC-transporter family are the most studied factors of the MDR phenomenon. According to the literature Pgp, MRP1, BCRP, and LRP are proteins involved in the development of the MDR. The authors detected the expression of these proteins in untreated patients with acute myeloid leukemia (other than M3). Expression of these proteins was observed in 64.3%, 46.4%, 64.3%, and 42.9% of patients, respectively. In all non-responders blast cells expressed more than one marker of MDR. Expression of 3 and 4 markers was found in 80% of non-responders while in responders 1—2 markers were expressed in 83%.